Well-Posedness and Stability Results for Lord Shulman Swelling Porous Thermo-Elastic Soils with Microtemperature and Distributed Delay - Choucha A.; Boulaaras S.; Jan R.; AbaOud M.; Alrajhi R. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The Lord Shulman swelling porous thermo-elastic soil system with the effects of microtemperature, temperatures and distributed delay terms is considered in this study. The well-posedness result is established by the LumerPhillips corollary applied to the HilleYosida theorem. The exponential stability result is proven by the energy method under suitable assumptions. 2023 by the authors.